Haptics. science, technology, and applications : 11th International Conference, EuroHaptics 2018, Pisa, Italy, June 13-16, 2018, Proceedings /: science, technology, and applications : 11th International Conference, EuroHaptics 2018, Pisa, Italy, June 13-16, 2018, Proceedings. Part II : (2018) - Unknown
No abstract available